Integrated Karyotypes of Diploid and Tetraploid Carrizo Citrange (Citrus sinensis L. Osbeck × Poncirus trifoliata L. Raf.) as Determined by Sequential Multicolor Fluorescence in situ Hybridization With Tandemly Repeated DNA Sequences - Deng, Honghong; Tang, Guohao; Xu, Nuo; Gao, Zhijian; Lin, Lijin; Liang, Dong; Xia, Hui; Deng, Qunxian; Wang, Jin; Cai, Zexi; Liang, Guolu; Lv, Xiulan (Frontiers in Plant Science, 2020)
Carrizo citrange [Citrus sinensis (L.) Osbeck × Poncirus trifoliata (L.) Raf., CC] is one of the most widely used rootstocks in citriculture worldwide, but its cytogenetic study has been hampered by its inherent small size, morphological similarity to mitotic chromosomes, and lack of accessible cytological landmarks. In our previous study, a spontaneously occurring tetraploid CC seedling was discovered. The main goals of this study were to elucidate the chromosome constitution and construct the karyotypes of diploid CC rootstock and its corresponding spontaneously occurring tetraploid. To accomplish these, the chromosomal characteristics were investigated by sequential multicolor fluorescence in situ hybridization (FISH) with eight properly labeled repetitive DNA sequences, including a centromere-like repeat, four satellite repeats, two rDNAs, and an oligonucleotide of telomeric (TTTAGGG)n repeat. The results nicely demonstrated that these repetitive DNAs are reliable cytogenetic markers that collectively facilitate simultaneous and unequivocal identification of homologous chromosome pairs. Based on chromosome size and morphology together with FISH patterns of repetitive DNAs, an integrated karyotype of CC rootstock was constructed, consisting of 2n = 2x = 12m (1sat) + 6sm with karyotype asymmetry degree being divided into 2B category. Cytogenetically speaking, the variable and asymmetric distribution patterns of these repetitive DNAs were fully confirmed the hybrid nature of CC rootstock. In addition, comparative distribution patterns and chromosomal localizations of these repetitive DNAs convincingly showed that this tetraploid CC material arose from somatic chromosome doubling of diploid CC rootstock. This study revealed, for the first time, the integrated karyotype and chromosomal characteristics of this important citrus rootstock as well as its spontaneously occurring tetraploid plant. Furthermore, this study is a good prospective model for study species with morphologically indistinguishable small chromosomes.